Forms and methods of specialist activity in criminal proceedings (Journal of actual problems of jurisprudence, 2018)
The article examines the problems of determining and using various forms and methods of a specialist’s activity in criminal proceedings. The procedural and non-procedural forms of his participation in criminal proceedings are subjected to analysis and theoretical and legal assessment.A clear understanding of the concept, content and types of forms of applying special knowledge in criminal proceedings is necessary for a successful investigation of any criminal case. The author cites in his work the opinions of various scholars regarding the definition and classification of forms and methods of applying special knowledge used in criminal proceedings. It should be noted that the level of knowledge necessary to resolve issues arising during the criminal process is constantly growing. This is due to the increasing use of the achievements of science and technology for criminal purposes. In order to successfully counteract developing crime, law enforcement officers must make the most of the opportunities and knowledge of a specialist in criminal proceedings. The possibilities of the conclusion and the testimony of a specialist in establishing the factual circumstances of a criminal case are quite large. At the same time, the use of these possibilities requires from investigators and judges a clear idea of how the conclusion and testimony of a specialist should be evaluated and how the facts established by this evidence should be assessed.Key words: criminal proceedings, specialist, special knowledge, methods of specialist activity, formsof applying special knowledge.